John R. Searle : thinking about the real world - Franken, Dirk; Karakuş, Attila; Michel, Jan G. (Münstersche Vorlesungen zur Philosophie (Series) ;, 2010)
John R. Searle is one of the world's leading philosophers. During his long and outstanding career, he has made groundbreaking and lasting contributions to the philosophy of language, to the philosophy of mind, as well as to the nature, structure, and functioning of social reality. This volume documents the 13th Münster Lectures on Philosophy with John R. Searle. It includes not only 11 critical papers on Searle's philosophy and Searle's replies to the papers, but also an original article by John R. Searle on his overall philosophical enterprise entitled ""The Basic Reality and the Human Realit.